Population and development issues in Bangladesh : national plan of action based on ICPD'94 recommendations - Barkat, Abul; Howlader, Sushil Ranjan (Ministry of Health and Family Welfare, Govt. of the People's Republic of Bangladesh, 1997)
Theme papers presented at a technical workshop held on December 17, 1996.